2008
DOI: 10.1177/154405910808700401
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Excretion of BisGMA in Guinea Pigs

Abstract: Bisphenol-A-glycidyldimethacrylate (BisGMA) is used in many resin-based dental materials. It was shown in vitro that BisGMA was released into the adjacent biophase from such materials during the first days after placement. In this study, the uptake, distribution, and excretion of [14C]BisGMA applied via gastric and intravenous administration (at dose levels well above those encountered in dental care) were examined in vivo in guinea pigs to test the hypothesis that BisGMA reaches cytotoxic levels in mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 14 publications
(17 reference statements)
0
32
0
Order By: Relevance
“…Consequently, non-crosslinked resin monomers can be leached out from the fillings by saliva, food or drinks 4,5) and reach the tissues of the oral cavity. These monomers can be inhaled or via the saliva reach the intestinal tract where they are absorbed by the small intestine and further metabolized [6][7][8][9][10] . Two main hypotheses how comonomers induce double strand breaks (DSBs) are currently discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, non-crosslinked resin monomers can be leached out from the fillings by saliva, food or drinks 4,5) and reach the tissues of the oral cavity. These monomers can be inhaled or via the saliva reach the intestinal tract where they are absorbed by the small intestine and further metabolized [6][7][8][9][10] . Two main hypotheses how comonomers induce double strand breaks (DSBs) are currently discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microscopic quantification of colocalizing γ-H2AX and 53BP1 foci has been used for NAC ameliorates dental composite-induced DNA double-strand breaks and chromatin condensation [39][40][41] . The metabolism of these substances was elucidated in animal studies using radioactively (C-14)-labeled (co)monomers [6][7][8][9] . It was noted that dental resin monomers can induce DSBs 29,30) and HEMA exposure can lead to apoptosis through oxidative DNA damage 42) , while Bis-GMA has been observed to induce morphological changes in human pulp cells including cellular contractions 43) .…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo and in vitro studies have unequivocally demonstrated that some components of composite resins and bonding agents exhibit toxic properties [10][11][12][13][14][15][16]. It is believed that basic monomers: bis-GMA and UDMA, as well as TEGDMA comonomer have high toxic potential [10,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The unreacted TEGDMA is a toxic substance exhibiting cytotoxic, genotoxic, mutagenic and allergenic effects [10]. It exhibits systemic and local toxicity on living organisms [10][11][12][13][14][15][16]. The interaction between composite materials, including TEGDMA, and exposed dental pulp is not fully known [10].…”
Section: Introductionmentioning
confidence: 99%
“…Resin monomers can be also directly degraded by salivary esterase [5]. The released BisGMA may be adsorbed from stomach and intestine and rapidly distributed to whole body [6]. It can be metabolized and excreted as BisGMA, methacrylic acid and bisphenol-A-bis(2,3-dihydroxypropyl)ether from the urine of experimental animals [7].…”
Section: Introductionmentioning
confidence: 99%